Enhancing severe accident management through research - Herranz Luis E.; Jiménez Gonzalo; Kärkelä Teemu (EPJ Nuclear Sciences & Technologies)
After the Fukushima Daiichi accident, a new wave of research projects aiming at enhancing severe accident (SA) management was launched under different international frameworks. This was the case of MUSA (Management and Uncertainties of Severe Accidents), AMHYCO (Towards and enhanced Accident Management of the H2 and CO combustion risk) and SOCRATES (Assessment of liquid Source Term for accidental post management phase), which under the frame of H2020 and HEUROPE EURATOM were devised to optimize different aspects of Severe Accident management. MUSA explored how bringing uncertainties quantification in the Severe Accident analysis might provide sounder insights into effects and timing of accident management actions. AMHYCO brought new insights into combustion risk management, particularly during the ex-vessel phase of the accident, by combining in a selective manner different analytical approaches and data on recombination and combustion of gas mixtures (i.e., H2/CO/air/steam). SOCRATES is hitting accident management related to liquid source terms, with emphasis in the long-run of the accident. This paper describes the major outcomes of the projects and outlines what should come next for an efficient application of the insights gained in the accident management.